PEP06 polypeptide 30 exerts antitumour effect in colorectal carcinoma via inhibiting epithelial–mesenchymal transition. (15th June 2018) - Yu, Siming; Li, Linna; Tian, Wei; Nie, Dan; Mu, Wei; Qiu, Fang; Liu, Yu; Liu, Xinghan; Wang, Xiaofeng; Du, Zhimin; Chu, Wen‐Feng; Yang, Baofeng
Abstract : Background and Purpose: PEP06, a polypeptide modified from endostatin, was investigated for its antitumour effects on colorectal cancer (CRC) and the possible mechanisms of this antitumour activity were examined in in vitro and in vivo models. Experimental Approach: After PEP06 treatment, cell proliferation and migration assays were performed in CRC cells. Epithelial–mesenchymal transition (EMT) progression was determined by Western blotting, immunofluorescent staining and immunohistochemistry in vitro and in a residual xenograft model. MiRNAs regulated by PEP06 were identified by miRNA microarray and verified by in situ hybridization and quantitative real‐time PCR. The interactions between PEP06 and integrin αvβ3 were determined with Biacore SA biochips. The cellular function of miR‐146b‐5p was validated by gain‐of‐function and loss‐of‐function approaches. A mouse model of lung metastasis was used to determine the effect of PEP06 on metastatic growth. Key Results: PEP06 did not affect cell viability but reduced migration and EMT in SW620 and HCT116 cells. PEP06 significantly repressed the expression of miR‐146b‐5p in these two cell lines through binding to integrin αvβ3. MiR‐146b‐5p was shown to increase EMT by targeting Smad4, and the miR‐146b‐5p‐Smad4 cascade regulated EMT in CRC. PEP06 also suppressed CRC pulmonary metastasis, increased survival of mice and hampered residual tumour growth by inhibiting EMT through down‐regulating miR‐146b‐5p. Conclusions and Implications: PEP06 is a polypeptide that inhibits the growth and metastasis of colon cancer through its RGD motif binding to integrin αvβ3, thereby down‐regulating miR‐146b‐5p to inhibit EMT in vitro and in vivo . It might have potential as a therapeutic for CRC.